Donor variation effect on red blood cell storage lesion: a multivariable, yet consistent, story. Issue 6 (29th March 2016) - Tzounakas, Vassilis L.; Georgatzakou, Hara T.; Kriebardis, Anastasios G.; Voulgaridou, Artemis I.; Stamoulis, Konstantinos E.; Foudoulaki‐Paparizos, Leontini E.; Antonelou, Marianna H.; Papassideri, Issidora S.
Abstract : BACKGROUND: Previous studies have shown that baseline hematologic characteristics concerning or influencing red blood cell (RBC) properties might affect storage lesion development in individual donors. This study was conducted to evaluate whether variation in hemolysis, microparticle accumulation, phosphatidylserine (PS) exposure, and other storage lesion–associated variables might be a function of the prestorage hematologic and biologic profiles of the donor. STUDY DESIGN AND METHODS: Ten eligible, regular blood donors were paired and studied before donation (fresh blood) and during storage of RBCs in standard blood banking conditions. Plasma and cellular characteristics and modifications were evaluated by standard laboratory and biochemical or biologic analyses as well as by statistical and network analysis tools. RESULTS: Nitrate/nitrite and other bioactive factors exhibited high interdonor variability, which further increased during storage in a donor‐specific manner. Storage lesion evaluators, including RBC fragility and PS exposure, fluctuated throughout the storage period in proportion to their values in fresh blood. Donors' levels of phosphatidylserine exposure and hemoglobin F correlated with stored cells' mean cell (RBC) Hb concentration, oxidative stress markers, and cellular fragility. DISCUSSION: Storage lesion indicators change in an orderly fashion, namely, by following donor‐related prestorage attributes. These correlations are illustrated for the first time in "prestorage versus storage" biologic networks, which might help determine the best candidates for in vivo biomarkers of storage quality and provide deeper insight into the apparently complex donor variation effect on the RBC storage lesion.